Smart retailing in cyberspace - (:unkn) unknown (Peter Lang Publishing Group, 2020)
In highly competitive business environment, brands are trying to differentiate themselves from the competitors and try to offer superior experience to their customers. Production is easy today. However, the problem is how to differentiate and sell these products. Retailers are playing an important role at this point. Many retailers today use smart technologies such as eye-tracking, shopping path recording, shopping cards, shelf-talkers, in-store TV and face recognition to enhance the consumer shopping experiences. New innovations enhanced by technology are on the way to serve the retailers. This chapter covers changes in consumer and retailing environment, smart retailing tools and future of retailing. © Peter Lang GmbH Internationaler Verlag der Wissenschaften Berlin 2020. All rights reserved.
Keywords: Future of Retailing; Marketing; Smart Retailing; Smart Technologies